The effectiveness of anaerob-aerob biofilters and phytoremediation using Pistia stratiotes for reducing TSS and AMONIAK content in noodle industry liquid waste - Yudi Ferdian Situmeang; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract                The noodle industry liquid waste is rich in Amoniak andTSS and thus need to be processed before being flown to environment. A research aims to reduce the Amoniak andTSS on liquid waste using biofilters has been conducted in March-April 2018. The noodle industry liquid waste (175 liters) was treated using a batch system that was consisted of 1 anaerob and 2 aerob tanks and a Pistia stratiotesphytoremediation pond. The liquid waste was kept for 10 ten days in anaerob tank with media gravel, sand and fibers. Then 7 days in aerob tanks with media chopped plastic bottle. Finally 15 days in a phytoremediation pondthat was completed withPistia stratiotes. By the end of the experiment, the Amoniak reduced from 9,4 mg/L to  3 mg/L (effectiveness 68.08%) and TSS reduced from 441 mg/L to 155 mg/L (effectiveness 64.85%). Other water quality parameter such as pH was normal and DO was improved. The treated waste was used for rearing Osphronemus gourami  (3-6 cm TL)and was kept for 15 days.The survival rate of the fish was 95%. Based on data obtained, it can be concluded that the combination of biofilters and phytoremediation system using Pistia stratiotes is effective to reduce the Amoniak and TSS content in thenoodle industry liquid waste. Keywords: Waste water,chopped plastic bottle media, batch system, waste management